2022
DOI: 10.2113/2022/9662175
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Dominant Factors for Natural Fractures in Deep Shale Gas Reservoirs: A Case Study of the Wufeng-Longmaxi Formations in Luzhou Block, Southern China

Abstract: In southern Sichuan Basin, the main production layers are characterized by deeply buried, high stress difference, and complex structural conditions. The Luzhou area is far from large faults, and natural fractures are greatly important for shale gas storage and production. Multi-scale natural fractures control the migration, enrichment, and preservation conditions of shale gas, and facilitate the formation of complex fracture network under the action of hydraulic fracturing. In this study, based on the outcrops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The fluid inclusions trapped in the uplift period confirmed that the Himalayan compression movement of Paleogene led to the opening of fracture vein and the adjustment and migration of shale gas. The early similar opening time with well H202 of fracture vein indicate that the damage degree was also similar, while the late stage opening of fracture vein led to the partial loss of shale gas. Therefore, the current pressure coefficient is 1.8. Although it is still in the overpressure state, its gas content is worse than that of well H202 (Figure ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The fluid inclusions trapped in the uplift period confirmed that the Himalayan compression movement of Paleogene led to the opening of fracture vein and the adjustment and migration of shale gas. The early similar opening time with well H202 of fracture vein indicate that the damage degree was also similar, while the late stage opening of fracture vein led to the partial loss of shale gas. Therefore, the current pressure coefficient is 1.8. Although it is still in the overpressure state, its gas content is worse than that of well H202 (Figure ).…”
Section: Discussionmentioning
confidence: 85%
“…The early similar opening time with well H202 of fracture vein indicate that the damage degree was also similar, while the late stage opening of fracture vein led to the partial loss of shale gas. 56 59 Therefore, the current pressure coefficient is 1.8. Although it is still in the overpressure state, its gas content is worse than that of well H202 ( Figure 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shale composition is an important factor affecting fractures, including mineral composition and content and TOC content (Ding et al, 2012;Zeng et al, 2013;Yin and Wu, 2020;Li, 2022). The statistical results show that with increasing quartz content, the fracture density increases first when the quartz content is less than 50%, while the fracture density decreases when the quartz content is over 50% (Han et al, 2022). Because of the positive relationship between TOC and quartz content, the relationship between TOC and fracture density also shows a similar trend (Han et al, 2022).…”
Section: Fracture Types and Controlling Factorsmentioning
confidence: 94%
“…The development of continental shale oil in China is still in its infancy. The shale oil horizontal wells in Block G in the Songliao Basin are affected by a lack of mature theories, technologies and experiences in the direction of wellbore stability [4][5][6][7][8]. The continental shale oil in the northern Songliao Basin has huge potential resources and has become an important strategic replacement resource in Daqing.…”
Section: Introductionmentioning
confidence: 99%